1997
DOI: 10.1046/j.1525-1497.1997.07126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an educational intervention on residents’ knowledge and attitudes toward interactions with pharmaceutical representatives

Abstract: To assess primary care resident and faculty knowledge and attitudes concerning interactions between physicians and pharmaceutical representatives (PRs) and to measure changes in residents' knowledge and attitudes after an educational intervention, we conducted preintervention and postintervention surveys with a causal-comparative group in a universitybased primary care residency program. All primary care internal medicine and internal medicine-pediatrics residents and faculty were given the voluntary survey. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…This may indicate the importance of good knowledge and correct attitudes about interactions with the pharmaceutical industry. It has been shown that education and discussion about the ethical issues related to exposure to pharmaceutical representatives can improve the attitudes of residents and medical students towards interactions (22)(23)(24)(25). Interestingly, knowledge and attitudes about interactions with the pharmaceutical industry in the current study was not significantly associated with having received ethics education.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate the importance of good knowledge and correct attitudes about interactions with the pharmaceutical industry. It has been shown that education and discussion about the ethical issues related to exposure to pharmaceutical representatives can improve the attitudes of residents and medical students towards interactions (22)(23)(24)(25). Interestingly, knowledge and attitudes about interactions with the pharmaceutical industry in the current study was not significantly associated with having received ethics education.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceutical detailing is restricted in many hospitals and medical clinics, especially in the teaching hospitals (McCormick et al, 2001;Lichstein, 1992;Brontzman and Mark, 1993;Education Council, 1993). Some studies show that the presence of restrictive departmental policies is associated with less favorable attitudes among physicians toward the value of interaction with PSRs (Brontzman and Mark, 1993;Sergeant, Hodgetts, Godwin, Walker, and McHenry, 1996;Hopper, Speece, and Musial, 1997). Therefore, the presence of a restrictive policy is expected to result in minimal use of pharmaceutical manufacturer-provided (promotional) information from any source including PSRs.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…These results show that physicians who see pharmaceutical sales reps more frequently are more likely to be invited by pharmaceutical companies to participate in e-detailing, compared to those who see pharmaceutical salespeople less frequently. Some studies show that high frequency of PSR visits usually is associated with more favorable attitudes among physicians toward the value of interaction with the pharmaceutical industry (Brontzman & Mark, 1993;Hopper, Speece, & Musial, 1997;Sergeant, Hodgetts, Godwin, Walker, & McHenry, 1996).…”
Section: Discussionmentioning
confidence: 99%